Mycotic aneurysm of suprarenal aorta in a 14-year-old boy - (:unkn) unknown (Asia Publishing Exchange Pte Ltd, 2000)
An extremely rare case of suprarenal mycotic aortic aneurysm of the abdominal aorta, secondary to tuberculous infection in a 14-year-old boy is reported. He required a Dacron graft implantation with visceral arterial reimplantation on an emergency basis. The patient died in the early postoperative period because of bleeding due to disseminated intravascular coagulation.